(untitled) (Jurnal Huma Betang Demokrasi, 2024)
Abstract Disputes regarding the results of the vote counting for regional head elections fall under the authority of the Constitutional Court. The polemic regarding the regional elections becomes interesting to discuss if seen from the juridical review of the Constitutional Court decision no. 149/PHP.GUB-XIV/2016 regarding allegations of structured, systematic and massive (TSM) election violations in the 2016 Central Kalimantan regional head election dispute decision. In this research, the researcher used normative legal research. The aim of this research is to look further into the reasons for the rejection of allegations of structured, systematic, and massive election violations (TSM) in the 2016 Central Kalimantan regional head election dispute decision. The results of this conclusion are strengthened by several reasons that can be seen in the Contents of the Ratio Decidendi The panel of judges at the constitutional court did not grant the applicant’s request in Constitutional Court Decision Number 149/PHP. GUB-XIV/2016. Keywords: Constitutional Court Decision; Regional Election Dispute. Abstrak Perselisihan sengketa hasil penghitungan suara pemilihan kepala daerah menjadi menjadi kewenangan MK. Polemik mengenai pilkada ini menjadi menarik untuk dibahas jika dilihat dari tinjauan yuridis pada putusan MK No. 149/PHP.GUB-XIV/2016 mengenai adanya dugaan pelanggaran pemilu yang bersifat terstruktur, sistematis, dan masif (TSM) pada putusan sengketa pemilihan kepala daerah Kalimantan Tengah tahun 2016. Dalam penelitian ini peneliti menggunakan jenis penelitian hukum normatif. tujuan dari Penelitian ini adalah untuk melihat lebih jauh alasan yang menjadi penolakan pada dugaan pelanggaran pemilu yang bersifat terstruktur, sistematis, dan masif (TSM) pada putusan sengketa pemilihan kepala daerah Kalimantan Tengah tahun 2016. Hasil dari kesimpulan ini diperkuat oleh beberapa alasan yang bisa dilihat pada Isi Ratio Decidendi Majelis hakim mahkamah konstitusi tidak mengabulkan permohonan pemohon pada Putusan Mahkamah Konstitusi Nomor 149/PHP. GUB-XIV/2016. Kata Kunci: Putusan MK; Sengketa Pilkada.